Analysis of Mountain Sand Material Content in Rumah Tiga and Hative Besar Villages, Teluk Ambon District Using X-Ray Diffraction (XRD) and X-Ray Fluorescence (XRF) Methods) - Sisca M Sapulete; Matheus Souisa; Amirah Hanifah; Ferdinanda C. Papilaja (Postgraduate, University of Mataram, 2023)
One area that has a mountain sand mine is Maluku, especially Ambon City, Teluk Ambon District, Hative Besar Village, and Rumah Tiga Village. This study aims to analyze mineral content, lattice parameters/crystal size, and the percentage of elemental and oxide content that forms a material on mountain sand in Wailete, Hative Besar Village and Kota Jawa, Rumah Tiga Village, using XRD and XRF methods. The mineral content analyzed by the XR-D method at both research locations showed the presence of diffraction peaks of the relationship between angle (2Î¸) and intensity (I) in the diffraction pattern with the main mineral content dominated by Quartz, Cristobalite, Sodalite, Calcite-synthetic, Anorthite, and followed by other minerals. Analysis of the percentage of elemental content using the XR-F method. Based on the results of XR-F analysis, the most dominant element in Wailete mount sand is Si (Silicon) with a percentage of 66.3% then followed by Al (Aluminum) at 10.8%, Fe (Iron) at 3.75% and in Kota Jawa hill, namely Si (Silicon) is 46.2%, Al (Aluminum) is 10.8%, Fe (Iron) is 9.11% and the rest is in the form of several elements with smaller percentages, namely Rb (Rubidium) and Sr (Strontium) 0.09%.